Defense Mechanism for Denial of Service Attack to UMTS Networks Using Sim-Less Devices (International Journal of Engineering and Computer Science, 2014)
One of the basic security element in cellular networks is the verification procedure functioned by means of subscriber identity module that is necessary to give access to network services and hence secure the network from unauthorized usage by implementing different types of parameters. The large amount of computing power available in modern clustered HLRs, it is also essential to consider the counter-intuitive result summarizes and showing that the more busy the HLR is, the more difficult is disrupting its services. The cellular infrastructure as a whole and thus in the measure needed by its defense, namely: 1.The complexity and the high level of programmability of latest mobile phones and 2.The interconnection between the cellular network and the internet. The awareness of this attack can be exploited by many applications both in security and in network equipment manufacturing sectors.